Capturing the invisible: Methodological approach in understanding informal cross border fish trade. (March 2023) - Ibengwe, Lilian J.; Onyango, Paul O.
Abstract: The lack of sufficient information about the magnitude of the informal cross-border fish trade (ICBFT) leads to underestimating the fisheries sector's importance to the national economy. Among other factors, this insufficiency is attributed to inconsistent methodologies applied to measure the ICBFT. This article presents a methodological approach drawn from 15 months of field experience in two border posts and one fishing village in mainland Tanzania to fill this gap. The proposed methodological approach integrates the insights of the grounded theory and social network analysis to form Networked Grounded methodological approach. The approach examined the ICBFT social network characteristics, identified an entry point for collecting accurate ICBFT data, and quantified the ICBFT weight and values of marine small pelagic fishery locally known as marine dagaa fishery. Findings indicate that the marine dagaa ICBFT social network involves 12 actors who nurture social network ties, translated into financial, emotional, and information social support, which is crucial for ICBFT operations. Overall, middlemen and porters were the key actors holding a significant role in facilitating ICBFT, attributed to being best networked to influential actors and as informers within the ICBFT network. Moreover, about 972 m. tons valued at US$ 1.8 million of informal marine dagaa were quantified, which was 843.2 m. tons higher than official statistics during the same period. These findings make a valuable contribution to the methodological approach that enables understanding of ICBFT, hence, informing management efforts and policy options, for effective management of the ICBFT and generate positive economic outcomes. Highlights: The five stepwise Networked Grounded (NG) methodological approach is drawn from 15 months of field experience studying Informal Cross Border Fish Trade (ICBFT). The NG methodological approach facilitates the identification of entry points for collecting reliable and accurate data on ICBFT. The NG methodological approach enables identifying ICBFT social network characteristics. The NG methodological approach can be adjusted and replicated in other fisheries systems according to that particular setting.